1997
DOI: 10.1088/0741-3335/39/6/001
|View full text |Cite
|
Sign up to set email alerts
|

Experimental divertor physics

Abstract: The physics of divertors in tokamaks is reviewed, primarily from an experimental point of view, although where possible simple analytic modelling is included. The paper covers the four main subject areas at issue in divertor research: (1) the wide dispersal of plasma power exhausted from the main plasma, (2) the production of sufficiently high gas pressures in the vicinity of pump ducts to enable the removal of fuel and helium ('ash') gas from the system, (3) the elimination or reduction of impurity production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
394
3
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 379 publications
(421 citation statements)
references
References 323 publications
(308 reference statements)
21
394
3
3
Order By: Relevance
“…In both attached and detached cases, the maximum velocity (at the plate) is considerably lower than the expected sound speed for the plasma ions, e.g. in the attached case the estimated sound speed is cs ~ 2 x 10' ms 1 based on the Langmuir probes, compared with a neutral velocity at the plate (chord 5) vH ~~ 5 x 10' ms- 1 . The situation is similar in the detached case, already discussed in the previous section.…”
Section: Ion-neutral Velocity Differentialmentioning
confidence: 93%
See 1 more Smart Citation
“…In both attached and detached cases, the maximum velocity (at the plate) is considerably lower than the expected sound speed for the plasma ions, e.g. in the attached case the estimated sound speed is cs ~ 2 x 10' ms 1 based on the Langmuir probes, compared with a neutral velocity at the plate (chord 5) vH ~~ 5 x 10' ms- 1 . The situation is similar in the detached case, already discussed in the previous section.…”
Section: Ion-neutral Velocity Differentialmentioning
confidence: 93%
“…One solution to this problem is the dissipative divertor, where a large fraction of the upstream power density is dispersed more uniformly by electromagnetic radiation, and possibly by neutral particles, see review [1]. Recent research has shown that the parallel power density at the target plate qit can be reduced from the upstream value by factors as large as -100, although factors of 5 to 10 are more typical.…”
Section: Introductionmentioning
confidence: 99%
“…The transport of particles and heat across them is of utmost importance for a variety of systems [4]. For example, much effort has been devoted by the fusion community in the past decades to investigate diverted magnetic geometries [5], which allow channeling through an X point a significant fraction of the exhaust power to material surfaces. Cross-field drifts associated with the steady-state and turbulence-induced electric fields play an important role for plasma transport in the X-point region, as indicated by numerical and experimental studies [6,7].…”
mentioning
confidence: 99%
“…Even the relatively pessimistic scaling r Γ ∝ 1/I p would still imply that Γ t r Γ ∝ I p 3/7 increases with plasma current. The ion saturation current is actually maximized at temperatures just above the point of detachment of plasma particle and heat fluxes from the target plate [29,30]. As discussed in Sec.…”
Section: E Scaling Of Perturbation Field With Upstream Sol Parametersmentioning
confidence: 92%
“…[29,30] with corrections for losses of momentum and power, is considered. The particle flux at the target is parameterized as Γ t = α t n t (T t /m i ) 1/2 where α t = ((T e + T i )/T t ) 1/2 and the heat flux is parameterized as q t = γ t p t (T t /m i ) 1/2 where γ t ∼ 5 − 10 is the sheath power transmission factor.…”
Section: E Scaling Of Perturbation Field With Upstream Sol Parametersmentioning
confidence: 99%